2015
DOI: 10.1111/ijpo.12062
|View full text |Cite
|
Sign up to set email alerts
|

Association of plasma fatty acid composition with plasma irisin levels in normal weight and overweight/obese children

Abstract: Metabolically unfavourable plasma FA profile was associated with higher plasma irisin level especially in overweight/obese children, suggesting that excess body fat might modulate these relationships.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 31 publications
0
7
1
Order By: Relevance
“…Furthermore, a recent study by Viitasalo et al has shown the association between increased irisin levels and a deteriorated lipid profile in children [35]. In a recent paper on obese children, the multivariate regression analysis showed that HDL-c had a significant association with the irisin plasma level [36], but our results indicated no association of irisin with HDL-c, LDL-c, triglycerides, and total cholesterol.…”
Section: Discussioncontrasting
confidence: 64%
“…Furthermore, a recent study by Viitasalo et al has shown the association between increased irisin levels and a deteriorated lipid profile in children [35]. In a recent paper on obese children, the multivariate regression analysis showed that HDL-c had a significant association with the irisin plasma level [36], but our results indicated no association of irisin with HDL-c, LDL-c, triglycerides, and total cholesterol.…”
Section: Discussioncontrasting
confidence: 64%
“…Despite, we previously reported that irisin plasma concentrations increased in children about obesity (10 children per group) with a positive correlation to the BMI percentile [14], and other reports showed an association between higher levels of irisin and an unhealthier FA profile [59]. In the present study, in a larger population, we observed that decreased irisin concentrations were associated with obesity but not with the FA profile since lower levels of irisin were associated with obesity even in the children with MUO that showed the worst FA profile.…”
mentioning
confidence: 72%
“…Additionally, higher proportions of oleic acid, adrenic acid, and docosapentaenoic acid in plasma were associated with higher plasma irisin levels among overweight/obese children, which suggests that irisin is directly associated with increased activity of elongation and desaturation steps following the desaturation of linoleic acid. A possible association between plasma irisin and delta-6-desaturase activity in plasma cholesteryl esters was also found [31], which has previously been reported to be associated with insulin-resistant states [32]. Excess body fat could modulate these relationships through fatty acid-mediated cross-talk between metabolically active tissues.…”
Section: Association Of Circulating Irisin With Cardiovascular Andmentioning
confidence: 97%